2019
DOI: 10.18502/ijnl.v17i3.368
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function, depression, and quality of life in patients with ruptured cerebral aneurysms

Abstract: Background: Neuropsychiatric dysfunction is one of the most common complications after aneurysmal subarachnoid hemorrhage (aSAH). The aim of this study was to evaluate cognitive function, depression, and quality of life (QOL) in patients with aSAH. Methods: In this study, we prospectively enrolled patients with SAH due to rupture of anterior circulation aneurysms who referred to Ghaem hospital, Mashhad, Iran, and who had good function outcome [modified Rankin scale (mRS) > 2]. They underwent microsurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Signi cant differences were observed in MoCA scores at 2 weeks and 1 month among the 5 groups, with signi cant differences between the right basal ganglia hemorrhage (BGH) group and cerebellar hemorrhage group at 2 weeks, indicating that BGH contributes more to cognitive impairment. Our ndings are consistent with previous studies suggesting that right basal ganglia damage impairs cognitive function by disrupting brain circuits and speci c cognitive abilities 13,17,18 . Nerve projection bers in the BG region through the anterior limb of the internal capsule are the frontopontine tract and anterior thalamic radiation, and damage to the BG interrupts the subcortical circulation of both the frontal and parietal lobes, leading to cognitive changes.…”
Section: Discussionsupporting
confidence: 93%
“…Signi cant differences were observed in MoCA scores at 2 weeks and 1 month among the 5 groups, with signi cant differences between the right basal ganglia hemorrhage (BGH) group and cerebellar hemorrhage group at 2 weeks, indicating that BGH contributes more to cognitive impairment. Our ndings are consistent with previous studies suggesting that right basal ganglia damage impairs cognitive function by disrupting brain circuits and speci c cognitive abilities 13,17,18 . Nerve projection bers in the BG region through the anterior limb of the internal capsule are the frontopontine tract and anterior thalamic radiation, and damage to the BG interrupts the subcortical circulation of both the frontal and parietal lobes, leading to cognitive changes.…”
Section: Discussionsupporting
confidence: 93%
“…A subarachnoid haemorrhage (SAH) can cause diverse symptoms for the individual, ranging from no to severe consequences, which is comparable to other types of stroke. However, the long‐term consequences described up to 4 years after SAH differ, and most SAH survivors have few physical symptoms and manage to complete their activities of daily living (ADL), but they still have several other symptoms that may affect their quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…An Iranian study on cognitive function, depression, and QoL in patients with aSAH reported that 57% and 55% of the patients developed cognitive impairment and depression, respectively. Additionally, age was positively correlated with the risk of post-SAH cognitive impairment, and SAH had long-term effects including, but not limited to, the inability of patients to return to work and integrate into society [ 16 ].…”
Section: Introductionmentioning
confidence: 99%